Tracking illegal wildlife trade in Papua, Indonesia: An initial investigation - Richard Gatot N. Triantoro; Agus Purwoko; Freddy Jontara Hutapea (Global Ecology and Conservation)
Wildlife trade is one of the main threats to wildlife, and it is considered one of the biggest challenges in wildlife conservation. Papua, the eastern part of Indonesia, is home to various wildlife where most of which are considered endemic. However, the pressure on wildlife sustainability in Papua is increasing due to habitat destruction and the wildlife trade. This study aimed to investigate wildlife trade in Papua, focusing on species identification, hunting and smuggling methods, price, and the trade chain. In this study, the term “illegal” refers to the hunting and trade activities without legal permission. The data were collected using a combination of underground techniques (for wildlife trade actors) and interviews with government agencies and informants at the airport. Interviews with 110 respondents (hunters, ex-hunters, collectors, ex-collectors, and sellers) revealed that 70 wildlife species were traded and transported outside Papua, where 25 species (16,800 individuals) were classified as illegal. Informants from the airport and government agencies added other 12 species, so in total, 82 wildlife species were commonly traded in Papua. The hunting method varied with the hunter’s ethnicity, where indigenous hunters used traditional equipment (arrows, spears, snares, and dogs) and non-indigenous people used snares, nets, catapults, and air rifles. Bird trade dominated by western black-capped lories (Lorius lory) was observed in all locations. More attention should be given to the pig-nosed turtle (Carettochelys insculpta) as it is heavily exploited for food, medicine, and ranching purposes. The growing market for jagal Papua (Cracticus cassicus) may also threaten its conservation status in the future. More actions are required to tackle wildlife trade in Papua, including mapping wildlife trade and hunting spots, intensifying monitoring at key sites, building networks with other institutions, and training local people to have alternative livelihoods.